Projeto e desenvolvimento de um sistema de monitoramento e controle utilizando arquitetura híbrida de comunicação - Medeiros, Emmanuel Leite de (2021)
One of the biggest challenges of water supply systems is to manage water resources appropriately and efficiently during the distribution. These systems are efficient when they use or implement tools that provide low water and energy consumption, low maintenance cost and supply water according to demand. However, there are many design problems related to water supply systems due to their dimensions and particularities, such as high cost of implementation and operation and lack of monitoring for different scenarios, resulting in problems such as leakage. According to a Brazilian research from Sanitation National Information System 39% of water is wasted due to leakage. The Industry 4.0 concept brings new techniques and technologies that benefit water supply systems and improve the monitoring and control of the industrial process, such as the Internet of Things (IoT). The IoT in industry systems allows the interconnection between sensors and actuators through telecommunication devices and brings benefits such as low costs of implementation and maintenance and increased coverage of sensing and performance. However, the poor signal strength of radio frequency devices, the low signal coverage and the high power consumption are some of the problems faced by wireless systems. Therefore, this work aims to develop an acquisition and control system with hybrid communication. The system has long-range, low-power (LoRa) modules, in addition to compatibility with various industrial protocols. The hybrid structure minimizes the cost of deployment with LoRa, as it allows the interconnection of sensors and actuator in the vicinity of the transmission point through cables.The LoRa used in the system allows a remote monitoring and control of water tanks, pipelines or water pump stations in areas without internet or mobile data coverage. The system transmission through LoRa reaches 1.1 km. The main results to be highlighted are the mean of measurement of 0, 78% and the remote triggering of control through a web server.